Pengembangan Soft Skill Siswa Dalam Kurikulum Merdeka Belajar Pada Mata Pelajaran Akidah Akhlak di MTSN 11 Agam - Mustika, Tiara; J, Junaidi; Karim, Hamdi Abdul; A, Arifmiboy (Madani: Jurnal Ilmiah Multidisiplin, 2025)
In the learning process, students do not only receive and listen to the teacher's explanation. Students are also required to participate actively in the learning process. By developing the soft skills within students. Developing soft skills in learning moral beliefs is one way of developing students' talents and interests in learning at school with teachers who play an active role in developing students' soft skills which can make students' skills develop. The aim of this research is to develop students' soft skills in the independent learning curriculum in the subject of moral beliefs at MTsN 11 Agam, to find out how teachers develop students' soft skills and the obstacles faced in developing soft skills through the independent curriculum in the subject of moral beliefs. This research is field research, with a qualitative descriptive approach. As for the key informants, namely the class VII Aqidah Akhlak teacher and supporting informants, namely class VII students and the principal of MTsN 11 Agam, the data collection techniques in this research are interviews, observation and documentation, to obtain data the data analysis used in the research is triangulation and references. The results of this research indicate that there is development of soft skills in moral aqidah lessons which are carried out to train students' communication skills. This soft skills development is carried out so that students have the forerunners for the future at a higher level of education. The obstacles in developing students' soft skills in this independent curriculum are also because this independent curriculum is a new curriculum and also depends on the teacher's professionalism in teaching. These soft skills are very influential in students, this is because students' soft communication skills depend on the student and how we develop the skills, talents and interests that exist within that person.